Introduction to information optics - Yu, Francis T. S. 1932-; Jutamulia, Suganda; Yin, Shizhuo, 1963- (San Diego : Academic Press, 2001)
While there are books treating individual topics contained in this book, this will be the first single volume providing a cohesive treatment on this subject as a whole. This goes beyond optical communications in that it includes related topics such as sensing, displays, computing, and data storage.
Entropy information and optics -- Signal processing with optics -- Communication with optics -- Switching with optics -- Transformation with optics -- Interconnection with optics -- Pattern recognition with optics -- Information storage with optics -- Computing with optics -- Sensing with optics -- Information display with optics -- Networking with optics.
Includes bibliographical references and index.
Keywords: Optical communications; Electronic books